Akibat Hukum Putusan Pailit terhadap Perseroan Terbatas dalam Kondisi Likuidasi: Studi Putusan Nomor 34/Pdt.Sus-Pailit/2024/PN Niaga Jkt.Pst - Permatasari, Yofi; Lie, Gunardi (Al-Ishlah: Jurnal Ilmiah Hukum, 2024)
This research aims to analyze the juridical validity of filing a bankruptcy petition against a State-Owned Company in liquidation and the legal consequences of a bankruptcy decision in such a context, based on a study of Decision Number 34/Pdt.Sus-Pailit/2024/PN Niaga Jkt.Pst. Employing a normative legal research method with a case study approach and qualitative-descriptive analysis of primary and secondary legal materials, this study finds that a State-Owned Company in liquidation retains its capacity as a debtor legal subject and can be declared bankrupt if the requirements under Law Number 37 of 2004 are met, particularly concerning the existence of at least two creditors and one payable that is due and simply collectible. The primary legal consequence of a bankruptcy decision in such a situation is the immediate cessation of the liquidation process previously conducted under Law Number 40 of 2007, accompanied by the complete transfer of authority for the management and settlement of the bankruptcy estate from the Liquidator team to the Curator appointed by the Commercial Court. This case study affirms that the bankruptcy mechanism can be legitimately applied to a State-Owned Company in liquidation, implying the supremacy of the Law Number 37 of 2004 regime to realize optimal collective protection for creditors.